ANALYSIS OF MAQÂSHID AL-SYARȊ’AH ON THE APPLICATION OF THE COLLATERAL IN THE MUDHȂRABAH CONTRACT IN SHARIA FINANCIAL INSTITUTIONS - Maman Surahman; Nurrohman Nurrohman (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2020)
In the study of classical Jurisprudence, the mudhârabah contract is the same contract which has no guarantee provisions in it. Therefore, in the mudhârabah contract there is no need for collateral, because the mudhârabah contract is a contract that is based on the element of trust (trust) so there is no need for guarantees given by customers to banks / Islamic financial institutions. The purpose of this study was to analyze maqâshid al- sharia on the application of collateral to the mudhârabah contract in Islamic Financial Institutions. The method of approach used in this study is normative juridical research with the nature of descriptive analysis. The type of data used in this study are primary and secondary data types. This research is classified as a type of qualitative research. The results show that collateral in the mudhârabah contract serves to avoid deviations from the fund management customer so that they do not play around in managing the mudhârabah financing fund, and guarantees are not necessary and mandatory conditions on every Mudhârabah financing. Therefore, LKS may set the guarantee to clients which serves to avoid the moral hazard of the mudharib negligent or not according to the contract, which is in line with the values of the benefit in Islamic transactions system.